Endometriosis increases the rate of spontaneous early miscarriage in women who have adenomyosis lesions. Issue 1 (January 2022) - Bourdon, Mathilde; Pham, Benjamine; Marcellin, Louis; Bordonne, Corinne; Millischer, Anne Elodie; Maignien, Chloé; Santulli, Pietro; Chapron, Charles
Abstract: Research question: In women with radiologically diagnosed adenomyosis, is the presence of endometriosis associated with a higher rate of miscarriage? Design: An observational cohort study of women who received medical care for benign gynaecological conditions between May 2005 and May 2018. Women who had adenomyosis lesions visualized by uterine magnetic resonance imaging (MRI) were included. Women who had never been pregnant were excluded. Women with adenomyosis identified by MRI but who did not have endometriosis lesions (control group) were compared with women with adenomyosis and endometriosis lesions (study group). Primary outcome was rate of a previous history of early miscarriage. Results: A total of 214 pregnancies in the study group and 53 pregnancies in the control group were analysed. The rate of a previous miscarriage was significantly higher among women with adenomyosis and endometriosis lesions compared with women in the control group (61/214 [28.5%] versus 6/53 [11.3%], respectively, P = 0.009). A multivariable generalized estimating equation logistic regression model, adjusted for adenomyosis and endometriosis phenotypes, found that the association between endometriosis and adenomyosis significantly increased the risk of miscarriage (OR 3.2, 95% CI 1.1 to 9.65). The risk was significantly higher with deep infiltrating endometriosis (OR 4.37, 95% CI 1.32 to 14.53). Conclusions: Women affected by endometriosis had a significantly higher rate of previous spontaneous miscarriage than women without endometriosis with adenomyosis lesions identified by MRI. Mechanistic studies are needed to establish the complex link between the presence of endometriosis and adenomyosis and the rate of spontaneous miscarriage.